Using Downside Risk Management Approach inDetermining Investment Strategies(An applied Study in Damascus Stock Exchange) (Journal of Al-Wataniya Private University, 2024)
This study aimed to identify the different strategies that investors can follow in managing and allocating assets, in addition to using different risk measures to determine the volatility resulting from investments in stocks listed on the Damascus Stock Exchange, based on historical data represented in the series of daily closing prices of the shares of all companies listed on the Damascus Stock Exchange from 1/1/2023 to 31/7/2024. The study found that there is a difference inthe investment strategies followed in Damascus Stock Exchange in terms of the stocks that can be acquired in each of them, due to the difference in the characteristics of the stocks, and the results of applying the criteria used to determine the degree of safety of the investment strategies followed. It was found through the use of semi-variance as a measure of risk that its values are low, which means that most of the fluctuations in the stocks returns' of companies listed in Damascus Stock Exchange are inthe positive direction, and when reviewing the conditional value at risk, it was relatively low, which indicates that the expected loss values with a 5% probability are small.Therefore, the conservative strategy can be considered the best among the strategies adopted and the most suitable for application in Damascus Stock Exchange.